Determination of Antioxidant Activities of Rhizomes of Laja Gowah (Alpinia malaccensis (Burm, F.) Roxb. - Sumiardi, Ade; Suryani, Nani; Marhamah, Siti (Proceeding International Conference on Global Resource Conservation, 2015)
Antioxidant is a substance that inhibits oxidation or reactions promoted by oxygen, peroxides, or free radicals. Antioxidants are also commonly added to food products such as vegetable oils and prepared foods to prevent or delay their deterioration from the action of air. Antioxidants may possibly reduce the risks of cancer. Â This study aimed to determine the antioxidant activities of rhizome of Laja Gowah (Alpinia malaccensis (Burm, F.) Roxb.) by using DPPH (1,1-Diphenyl-2-Picrylhydrazyl) methods. Laja Gowah (Alpinia malaccensis (Burm, F.) Roxb. ) is classified into family of Zingiberaceae. Extraction is done by maceration with methanol solvent and fractionation by using a funnel with a solvent which has different levels of polarity, namely the n-hexane and ethyl acetate. Qualitative analysis is measured by thin layer chromatography for fraction methanol, n-hexane and ethyl acetate. All fraction showed the presence of flavonoids and terpenoids which is marked by appearing yellow and purple spots after reacting by H2SO4 10%. Determination of antioxidant activities from the each fraction showed that all fractions have potential function as an antioxidant with LC50 values. Fraction of n-hexane showed 72.03 ppm, fraction of ethyl acetate showed 96.31 ppm, and fraction of methanol showed 194.43 ppm. For comparison, ascorbic acid has antioxidant activities with IC50 values as many as 2.23 ppm.Keywords: Alpinia malaccensis; antioxidant; 1,1-diphenyl-2-picrylhydrazyl